Evaluación de errores de posicionamiento en los 6 grados de libertad en pacientes con cáncer de próstata tratados con radioterapia (2021)
Objectives: To determine the magnitude of the positioning errors in the 6 degrees of freedom and calculate the Margin to CTV for an adapted protocol in patients with early and locally advanced prostate cancer in a reference center in Colombia. Methods: A